KADAR KALIUM DI PACKED RED CELLS SIMPANAN - Angeline Sutjianto; Asvin Nurulita; Fitriani Mangarengi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Blood transfusion, is not only transferring the blood cells to the recipient, but also transferring other components such as: glucose,lactate, and potassium. When the blood is stored, many alterations occur in its cmponents, particularly a decrease of adenosine5-triphosphate (ATP) and pH, hemolysis, and an increase of potassium levels as well. One of the transfusion complications that should beavoided is hyperkalemia due to the accumulation of potassium that leaks during the storage. However, hyperkalemia related to transfusiondepends not only on the potassium level in the blood unit, but also on its volume and the rate of its blood administration as well. Theaim of this study was to know the potassium levels in stored Packed Red Cell (PRC). A cohort study was done from May–July 2010. Theresearchers used 48 samples from 16 PRCs derived from 16 donors. The samples were drawn from the of PRC hose’s plasma that had beensealed. The potassium levels were measured on the first day, 10th day, and 20th day of the blood collection. The mean potassium levelon the first day was 3.79 mmol/L, 10th day was 12.22 mmol/L and 20th day was 19.77 mmol/L. Comparison of the potassium levelsbetween the first and 10th day, between first and 20th day, and between 10th and 20th day showed a significant difference (p=0.00). Theincrease of potassium levels in the PRC coincide with the storagetime.